Breathing retraining for dysfunctional breathing in asthma: a randomised controlled trial. Issue 2 (1st February 2003) - Thomas, M; McKinley, R K; Freeman, E; Foy, C; Prodger, P; Price, D
Abstract : Background: Functional breathing disorders may complicate asthma and impair quality of life. This study aimed to determine the effectiveness of physiotherapy based breathing retraining for patients treated for asthma in the community who have symptoms suggestive of dysfunctional breathing. Methods: 33 adult patients aged 17–65 with diagnosed and currently treated asthma and Nijmegen questionnaire scores ⩾23 were recruited to a randomised controlled trial comparing short physiotherapy breathing retraining and an asthma nurse education control. The main outcome measures were asthma specific health status (Asthma Quality of Life questionnaire) and Nijmegen questionnaire scores Results: Of the 33 who entered the study, data were available on 31 after 1 month and 28 at 6 months. The median (interquartile range) changes in overall asthma quality of life score at 1 month were 0.6 (0.05–1.12) and 0.09 (−0.25–0.26) for the breathing retraining and education groups, respectively (p=0.018), 0.42 (0.11–1.17) and 0.09 (−0.58–0.5) for the symptoms domain (p=0.042), 0.52 (0.09–1.25) and 0 (−0.45–0.45) for the activities domain (p=0.007), and 0.50 (0–1.50) and −0.25 (−0.75–0.75) for the environment domain (p=0.018). Only the change in the activities domain remained significant at 6 months (0.83 (−0.10–1.71) and −0.05 (−0.74–0.34), p=0.018), although trends to improvement were seen in the overall score (p=0.065), the symptoms domain (p=0.059), and the environment domain (p=0.065). There was a correlation between changes in quality of life scores and Nijmegen questionnaire scores at 1 month and at 6 months. The number needed to treat to produce a clinically important improvement in health status was 1.96 and 3.57 at 1 and 6 months. Conclusion: Over half the patients treated for asthma in the community who have symptoms suggestive of dysfunctional breathing show a clinically relevant improvement in quality of life following a brief physiotherapy intervention. This improvement is maintained in over 25% 6 months after the intervention.